Organizational structure and procedure barriers to obedizing Philippine higher education: Implications to policies and practice - Dagdag, Januard Denola (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2020)
The claim that higher education institutions are outcome-based education-aligned or obedized necessitates evidence in practice. This policy perspectives article discusses the implications of the following prevailing inputs-based structures and procedures to the implementation of outcome-based education in Philippine higher education: (1) segmenting learning time and prescheduling examination; (2) covering curriculum contents over achieving desired outcomes; (3) imposing regular classroom meetings; (4) quantifying inputs targets; (5) quantifying learning performance using a mark; (6) aligning assessments with the licensure examination; (7) and screening and clustering students through a test. The paper offers insights necessary for strengthening policies and practice to obedizing tertiary education in the Philippines and beyond.